2020
DOI: 10.18632/aging.103499
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics network analysis reveals distinct stages in the human aging progression in epidermal tissue

Abstract: In recent years, reports of non-linear regulations in age-and longevity-associated biological processes have been accumulating. Inspired by methodological advances in precision medicine involving the integrative analysis of multi-omics data, we sought to investigate the potential of multi-omics integration to identify distinct stages in the aging progression from ex vivo human skin tissue. For this we generated transcriptome and methylome profiling data from suction blister lesions of female subjects between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…In addition, the sample size of the LTPA discordant twins is limited, and therefore, statistical power to detect small effects may be insufficient. It should be noted that recent studies have shown that biological aging may be distinct stages rather than a continuous process, and aging progression may not be linear throughout the studied age ranges ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sample size of the LTPA discordant twins is limited, and therefore, statistical power to detect small effects may be insufficient. It should be noted that recent studies have shown that biological aging may be distinct stages rather than a continuous process, and aging progression may not be linear throughout the studied age ranges ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were aged between 30 and 65 years, with homogenous age distributions in each phototype group. Similar to previous studies 71 , exclusion criteria included tattoos or scars in the test area, pigmentation disorders, pregnancy and medication such as anti-histamines or anti-inflammatory drugs within two weeks prior to study start. A detailed listing of exclusion criteria can be found in the Supplementary information.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acid extraction was performed as previously described 71 . Tissue samples were suspended in the respective lysis buffers for DNA or RNA extraction and homogenized using an MM 301 bead mill (Retsch).…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells exhibit two distinct peaks of rapid epigenomic changes in humans: one around 40 years of age and another around 60-70 years of age 36 . Likewise, a longitudinal study of the transcriptome and DNA methylation state of skin in 121 humans between 21 and 76 years of age revealed four distinct phases of aging highlighted by the activity of different biological processes 37 . Interestingly, functional MRI measurements of brain connectivity seem to support these asynchronous molecular measurements, showing nonlinear changes and transition points around the ages of 40 and 70-75 years of age 38 .…”
Section: Box 2 | What Is Aging?mentioning
confidence: 99%